2013 IEEE Business Engineering and Industrial Applications Colloquium (BEIAC) 2013
DOI: 10.1109/beiac.2013.6560091
|View full text |Cite
|
Sign up to set email alerts
|

Exploring lean construction components for Malaysian construction industry

Abstract: Malaysian construction industry is suffering problem of producing high wastage and low productivity. Lean construction is an approach which is feasible to cope with the situation and it will be more significant to be applied by all players in Malaysian construction industry. Thus, this paper is to review the lean construction concept and components which are applicable in Malaysian construction industry. It was found that lean construction components comprise of principles, criteria and tools. Components are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Nevertheless, lean construction employs the same principles as lean manufacturing to minimise construction waste and maximize productivity, efficiency and effectiveness in order to produce the greatest amount of value possible in construction projects by reducing NVAA in all phases of project delivery (Aziz and Hafez, 2013;Marhani et al, 2013;Smith, 2015;Khodeir and Othman, 2018;Tezel, Koskela and Aziz, 2018;Mohammadi et al, 2020). In order to become a successful construction firm, the application of lean tools is paramount (Sacks, Radosavljevic and Barak, 2010;Aziz and Hafez, 2013;Muhammad, Ismail, and Hashim, 2013;Sarhan and Fox, 2013). Therefore, not only minimising the impact of the COVID-19 pandemic but also immense benefits will provide for the construction organisations through post-COVID lean implementation as presents in the following Table 2.…”
Section: Integration Of Lean Constructionmentioning
confidence: 99%
“…Nevertheless, lean construction employs the same principles as lean manufacturing to minimise construction waste and maximize productivity, efficiency and effectiveness in order to produce the greatest amount of value possible in construction projects by reducing NVAA in all phases of project delivery (Aziz and Hafez, 2013;Marhani et al, 2013;Smith, 2015;Khodeir and Othman, 2018;Tezel, Koskela and Aziz, 2018;Mohammadi et al, 2020). In order to become a successful construction firm, the application of lean tools is paramount (Sacks, Radosavljevic and Barak, 2010;Aziz and Hafez, 2013;Muhammad, Ismail, and Hashim, 2013;Sarhan and Fox, 2013). Therefore, not only minimising the impact of the COVID-19 pandemic but also immense benefits will provide for the construction organisations through post-COVID lean implementation as presents in the following Table 2.…”
Section: Integration Of Lean Constructionmentioning
confidence: 99%
“…Operations are scrutinized thoroughly, bringing ideas and suggestions to explore the alternative of doing the task. The PDCA (plan, do, check, and act) cycle is used to build up the first-run study [23].…”
Section: First Run Studiesmentioning
confidence: 99%
“…The Last Planner System (LPS) is one of the tools used in LC which produces anticipated and dependable workflow and fast learning in programming, design, construction, and commissioning of projects [23].…”
Section: The Last Planner System (Lps)mentioning
confidence: 99%
See 1 more Smart Citation
“…To face the problems, organisation should be find the best of lean manufacturing tools and technique. Lean manufacturing tools and techniques play a vital role in the effective development process in reducing process completion time, hours, design and supply chain management integration, process control, flexibility, environmental sustainability and increased the quality of products [71][72][73][74]. In an analysis of lean manufacturing tools and technique, Schweikhart and Dembe [75] found that the successful or failure in any companies is based on the proper prioritisation and the choice of appropriate lean tools.…”
Section: Stage 2: Domentioning
confidence: 99%